PENGGUNAAN METODE ILEARNING UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN DI PERGURUAN TINGGI - Henderi Henderi; Muhamad Yusup; Yulika Ayu Rantama (Universitas Raharja, 2013)
One of the problems faced by universities noday is still a lack of learning systems that can support good teaching and learning quality and efficient. Currently, there are still learning methods which are conventional in which learning is still running in one direction, where the student fixated on material submitted by the lecturer in front and make the student tend to feel tired and passive. As an alternative to solving the problem is to provide the latest teaching innovations iLearning System (Integrated Learning), or in Indonesian called integrated learning system that is applied is one form to improve the quality to a modern and quality education. The reason the application of this method of learning iLearning we hope to provide a learning system that is more active and has a strong reciprocity between faculty and students, because the learning process of innovative and efficient will certainly add to the fun and spirit of the student so that the student was will not feel bored and passive. Using iLearning student can learn more optimally, they can see and read materials provided by lecturers in their respective iPad. Not only that students can easily do exercises / quiz, browsing, sending tasks, discussed and recorded with iPad without having to spend a stationery. Given these practical learning may help in improving the quality of learning activities based iLearning on Higher Education, and eventually gained a graduate or Human Resources (HR) that are reliable and able to compete in an era of globalization characterized by high competition.